A Collaborative Study on the Measurement of Protein S Antigen in Plasma - Hubbard, Anthony R; Wong, Man Yu (Thrombosis and Haemostasis, 1992)
A collaborative study on the measurement of protein S (PS) antigen (total and free) in a freeze-dried ampouled test plasma by assay against local house standard plasmas was carried out in eleven laboratories. Potency estimates of total PS showed good agreement between laboratories with a geometric coefficient of variation (gcv) of 5.9% and an overall combined potency of 0.84 units per ml. Potency estimates of free PS antigen in the test sample were associated with increased variability between laboratories resulting from the polyethylene glycol (PEG) precipitation step which is used to separate free PS from PS bound to the C4b binding protein. Free PS in the test could be expressed relative to either total PS in the house standards (e. g. 0.28 units per ml) or relative to free PS in the house standards following PEG precipitation (e. g. 0.71 units free PS per ml).